ANALISIS KEUNTUNGAN PENGRAJIN TAHU BERDASARKAN CARA PEMBAYARAN DI KECAMATAN MALALAYANG, KOTA MANADO - Melkias ., Londo; Noortje M. Benu; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2017)
The objective of this research is to compare the benefits received of tofu before and after the increase in soybean prices in the payment system: payment system prior to production and after to production. This research was conducted in June to November 2016. The data used are primary data obtained through interviews of 10 (ten) respondents and secondary data obtained from the Malalayang Sub-district Office and the office of Service Industry at the Manado City. Analysis of the data used is the analysis of business advantage. The research result indicate that the increase in soybean prices resulted in a decrease of 14.28 percent profit amounted to -9.46 percent tofu for a businessman who uses a payment system prior to production and craftsmen who use the payment system after production decreased to -22.04 percent, the difference between the profit decline of tofu businessman that using a payment system before production and after production amounted to 12.58 percent. *jnkd*.